A portable aerosol monitor with a novel linear deconvolution algorithm for fast and accurate detection of alpha emitters - Ferrante Vero Luca F.; Manessi Giacomo P.; Marzo Giuseppe A.; Zorloni Gabriele (EPJ Web of Conferences, 2023)
Radiochemistry laboratories and nuclear power plants are required to install aerosol monitors for real-time detection of alpha-particle emitters in air. However, common radioactive aerosol monitors are unsuited for rapid emergency response, since they are neither portable nor easily deployable. Moreover, their spectrometric capabilities are usually limited, showing particularly poor performance of radioisotope identification, which makes it difficult to correctly assess the alpha-emitter concentration in air. We developed a rugged and compact radioactive aerosol monitor, fully battery powered, which can be quickly deployed in field, as well as used as a fixed station for routine monitoring. The monitor is equipped with a silicon detector, and the acquired alpha-particle spectra are analyzed employing a patented linear deconvolution algorithm. A prototype of this device was tested to evaluate its performance of radioisotope identification by using artificial alpha-emitters. Initial encouraging tests provide evidence for alpha-emitters identification with multi-line mixed-isotope alpha sources, and in energy-degraded low-countingstatistics conditions.